Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 11 - Cumulative Review - Page 835: 29


$4-2\sqrt 3$

Work Step by Step

$(\sqrt 3-1)^{2}$ =$(\sqrt 3-1)(\sqrt 3-1)$ =$\sqrt 3(\sqrt 3-1)-1(\sqrt 3-1)$ =$3-\sqrt 3-\sqrt 3+1$ =$3+1-\sqrt 3-\sqrt 3$ =$4-2\sqrt 3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.